Thoracic fascial planes blocks in operative bed of modified radical mastectomy and their role in alleviating post-mastectomy pain: a prospective randomized study - Abdelhalim, Mohamed F.; Elbegawy, Mohamed A. (International Surgery Journal, 2021)
Background: Proper pain management after modified radical mastectomy is crucial for improving postoperative outcomes, reducing tumor recurrence, enhancing anti-metastatic activity and achieving excellent patient`s satisfaction. Thoracic fascial planes (TFP) blocks are novel, and safe analgesia modalities to control postmastectomy pain. This study was designed to assess the efficacy and safety of intraoperative TFP blocks for providing postoperative analgesia after modified radical mastectomy. Methods: During the period from March 2020 to April 2021, 30 females (ages 25–67 years) were scheduled for elective MRM and selected randomly to one of two groups; group-A included 15 patients who underwent MRM and anesthetized with both general anesthesia and regional anesthesia (TFP blocks), group-B included 15 patients who underwent MRM and anesthetized with only general anesthesia. Results: The group-A had statistically significantly lower pain scores. The time of first rescue nalbuphine dose post-operatively was statistically significantly longer in group-A compared to group-B. The total 24h nalbuphine consumption and postoperative non-steroidal ketorolac requirements/48h were significantly lower in group-A compared to group-B. Satisfaction score in group-A was statistically significantly better than that in group-B. Conclusions: Intraoperative thoracic fascial planes blocks are simple, safe, and highly effective analgesic modalities after breast surgery.